Pembinaan Kader Posyandu dalam Pencegahan Stunting: Pembinaan Kader Posyandu dalam Pencegahan Stunting - Hasmia Naningsih; Khalidatul Khair Anwar; Aswita Aswita (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
Nutritional status becomes very important considering the critical period of growth in the first 2 years is a period for the growth and development of a child. Malnutrition in children is a major public health problem in developing countries, including Indonesia. One of the nutritional deficiencies in children is stunting. The stunting rate in Southeast Sulawesi Province in 2021 was around 30,2%. One of the causes of stunting is the lack of understanding of parents on nutritional intake during pregnancy and the fulfillment of nutrition in infants. Posyandu cadres as one of the closest people to the community have an important role in providing information. However, the provision of health information that really needs to be supported by empowerment or training for posyandu cadres. Based on initial survey data, training for Posyandu cadres in the Soropia Health Center working area regarding stunting had never been carried out. The purpose of the activity is to increase the knowledge of cadres about stunting. The activity involved the coordinating midwife at the Soropia Health Center and the cadres of the Posyandu in Soropia District, which was 20 people as the target of coaching. The results of the service show that the average knowledge pre-test score is 60.00 and the knowledge post-test average value is 90.00. The results of the work can be obtained by increasing the knowledge of cadres. Therefore, it is hoped that training activities for posyandu cadres can be carried out every year so that cadres can educate mothers and their families so that they can detect early if there is stunting.